The Effectiveness of Plastic Recycling Montage in Stimulating Creativity of Children Aged 5–6 Years - Fadilah, Yuliatul; Yuandana, Tarich (Nak-Kanak: Journal of Child Research, 2025)
Background of the study: Creativity in early childhood has not developed optimally, as many learning activities still rely on worksheets. Developing creativity is crucial, as it fosters not only the ability to produce creative works but also critical thinking skills, enabling children to provide alternative solutions to problems in their daily lives. Aims and scope of paper: This study aims to examine the effectiveness of plastic recycling montage activities in stimulating the creativity of children aged 5–6 years. Methods: This study employed a quantitative approach with an experimental method using a pre-experimental one-group pretest–posttest design. The research was conducted at TK Bunda Burneh Bangkalan in Class B, involving 34 children aged 5–6 years. The study was carried out in three phases: preliminary study, implementation, and data processing, starting on November 18, 2023. Data were collected through observation, interviews, and documentation, supported by relevant literature from accredited journals, articles, and books. Data analysis involved prerequisite tests, including normality (Shapiro–Wilk) and homogeneity tests, followed by a t-test and N-Gain score analysis to determine the effectiveness of plastic montage recycling in stimulating children’s creativity. Results: The findings indicated a significant increase in children’s creativity after participating in plastic recycling montage activities. The N-Gain Score result was 0.853, which falls into the “high” category, showing that the activity effectively stimulated creative abilities in early childhood. Contribution: This study contributes to early childhood education by providing evidence that plastic recycling montage activities can serve as an innovative and effective approach to fostering creativity. Such activities not only enhance creative expression but also support the development of critical thinking and problem-solving skills in young children.